Molecular cloning and characterization of a novel tomato xylosyltransferase specific for gentisic acid - Tárraga, Susana (Journal of experimental botany, 2010)
The importance of salicylic acid (SA) in the signal transduction pathway of plant disease resistance has been well documented in many incompatible plant-pathogen interactions, but less is known about signalling in compatible interactions. In this type of interaction, tomato plants have been found to accumulate high levels of 2,5-dihydroxybenzoic acid (gentisic acid, GA), a metabolic derivative of SA. Exogenous GA treatments induce in tomato plants a set of PR proteins that differ from those induced by salicylic acid. While SA accumulates in tomato plants mainly as 2-O-β-D-glucoside, GA has only been found as 5-O-β-D-xyloside. To characterize this step of the GA signalling pathway further, the present work focuses on the study of the GA-conjugating activity in tomato plants. A gentisate glycosyltransferase (GAGT) cDNA has been isolated and overexpressed in Pichia pastoris, and GA-conjugating activity was confirmed by detecting the xylosylated GA. The purified plant protein is highly specific for GA, showing no activity toward many other phenolic compounds, including SA. In addition, it shows an outstanding selectivity for UDP-xylose as the sugar donor, which differentiates this enzyme from most glycosyltransferases. Both the GA-conjugating activity and the corresponding mRNA show a strong, rapid, and transient induction upon treatment of tomato plants with GA or SA. Furthermore, its expression is rapidly induced by compatible infections. However, neither the gene nor the activity seems to respond to incompatible infections or wounding. The unique properties of this new glycosyltransferase suggest a specific role in regulating the free GA levels in compatible plant-pathogen interactions